KARAKTERISTIK SENYAWA BIOAKTIF EKSTRAK SELADA LAUT (Ulva lactuca L.) PADA KONSENTRASI PELARUT ETANOL DAN LAMA EKSTRAKSI - Dina Yunita, Ni Luh Gede; Wrasiati, Luh Putu; Suhendra, Lutfi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 6 No 3 (2018): SeptemberDO - 10.24843/JRMA.2018.v06.i03.p01, 2018)
Ulva lactuca  L. is a type of Chloro   phyta or green algae. Ulva lactuca  L. contains many chemical compounds that are useful to be developed. This study were determine the effect of ethanol solvent concentration and duration of extraction on the characteristics of extract bioactive compounds. This study used Factorial Randomized Block Design (RAK) with 2 factors as treatment. Factor I is the concentration of ethanol solvent which consists of 3 levels there are 70%, 80% and 90%. Factor II is the length of extraction consisting of 4 levels there are 3 hours, 4 hours, 5 hours, and 6 hours. The results showed that ethanol solvent concentration and extraction time were very influential on total phenolic content of sea lettuce extract. While the interaction treatment of ethanol concentration and extraction time greatly affect the levels of vitamin C and ?-tocopherol levels. Ethanol concentration of 90% and 5 hours extraction time resulted in the best extract of Ulva lactuca  L. with characteristics of vitamin C content of 35.64 mg / 100g., Total phenolic 694.57 mg GAE / 100 g, and ?-tocop herol content of 308.54 mg / 100g. Keywords : Ulva lactuca  L , solvent concentration, extraction time, vitamin C, phenolic ?-tokoferol